Impact of Home-Centered Care on Type 2 Diabetes Mellitus: A Comprehensive Review - Burair Hassan Alqambar et al. (International Journal of Scientific Research and Innovative Studies, 2024)
Type 2 diabetes mellitus (T2DM) is a prevalent chronic condition with a growing global burden, requiring sustainable management strategies that extend beyond clinical settings. Home-centered care (HCC), which focuses on patient management within the home environment, has emerged as a transformative approach. This review explores the impact of HCC on glycemic control, lifestyle adherence, psychological well-being, and healthcare costs. It highlights the benefits of personalized care, technological advancements, and family engagement in managing T2DM. Additionally, it addresses the challenges of implementing HCC, including resource allocation, caregiver burden, and health inequities. HCC has proven effective in enhancing patient outcomes and satisfaction, offering a pathway for comprehensive diabetes care in the future. Received Date: July 08, 2024 Accepted Date: July 29, 2024 Published Date: August 01, 2024 Available Online at: https://www.ijsrisjournal.com/index.php/ojsfiles/article/view/293 DOI: https://doi.org/10.5281/zenodo.14559998